Ecology and Pneuma: Needing and Finding Each Other? - Lombard, Christo (Journal of Reformed Theology, 2012)
Abstract A discussion of early contributions on ecological spirituality, such as 'rediscovering the Gospel of the Earth' (Tom Hayden), 'telling a New Universe Story' (Thomas Berry) and 'religion as roots and wings' (Jay McDaniel), serves as sounding board for the much earlier pneumatological reflections on humanity and nature by the Dutch scholar, A.A. van Ruler. In his Trinitarian theology, Van Ruler explored ways of overcoming dualism in Christianity and countering spiritless definitions of reality in science. Christology and 'incarnation' need supplementation by Pneumatology and indwelling' of God's Spirit in humanity and nature to eschatologically properly integrate 'all things' in God's ecology.
Paid
Keywords: A.A. van Ruler; BERRY; Thomas; 1914-2009; ECOLOGY; HAYDEN; Tom; 1939-2016; HUMANITY; SOUL; SPIRITUALITY; Thomas Berry; Tom Hayden; ecology; pneuma